A epistemologia da formação de professores de educação especial: um professor plurivalente para “dar conta da inclusão”? - Thesing, Mariana Luzia Corrêa (2019)
This doctoral thesis was developed in the Special Education, Inclusion and Difference Research Line, in the Strictu Sensu Doctoral Course, of the Graduate Program in Education (PPGE) of the Federal University of Santa Maria (UFSM-RS). The main objective of the study was to know and analyze the epistemological basis of the Diurnal Special Education Undergraduate Course of the Federal University of Santa Maria, during the period from 1980 to 2008, the period of the last reformulation of its curricula, and to verify to what extent they are related to the proposition to the teaching work of these teachers in their different professional contexts.With this central objective, it aims, from specific objectives, to understand what are the relations between teacher education and the proposition to the work of these teachers, considering the multiple functions assumed by these teachers in school spaces; understand the relationship between educational legislations and the formation of special education teachers of the Undergraduate Course of Daytime Special Education at UFSM; and in understanding the role of the Special Education teacher in their work contexts. The proposed research is based on the assumptions of dialectical materialism and with a qualitative approach, is configured as a case study. As methodological instruments, narrative interviews were listed with five teacher trainers and ten graduated teachers; and also the collection and study of documents related to the historicity of the course, considered pertinent to the studied problem. Data analysis is proposed based on content analysis, document analysis and methodological triangulation. From the analysis of the teachers' narratives and the menus of the subjects offered in the current curriculum, it is clear a course characterized by the formation of teachers with a psycho-pedagogical epistemological basis, from the interactionist / sociointeractionist perspective of learning, which intends to look at the disabled subject as a learning subject, from its biopsychosocial possibilities.This perspective is opposed to the proposition of the previous curriculum, interested in training teachers with a medical-therapeutic epistemological base, focused on the study of techniques and resources with the purpose of rehabilitating the subjects with disabilities for life in society.The relationship between formation and proposition to the work was expressed in the statements of the teachers participating in this research, which revealed the condition of a teacher who needs to “handle” different demands in the pedagogical work, believing in the possibility of inclusion of subjects with disabilities in the regular school, despite the lack of material conditions for its realization. As conclusions, the proposition is presented that the course aims at the formation of teachers with a historical-critical basis, in which the discussions would be centered on social practice, in a pedagogical perspective that understands the educational act as a process in which subjects have an active relationship with each other and with the world. From this perspective, working with knowledge in the formative process would be aimed at training education professionals committed to the democratization of knowledge in school, which would be a tool for the struggle for the emancipation of men and women in the historical times in which we live.